Mou Zongsan's concept of Immanent-transcendence - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2021)
This paper examines the meaning and importance of the concept of immanent-transcendence in Mou’s assertion that Chinese philosophy is unique and superior, through his engagement with the philosophy of Immanuel Kant and his comparisons of Chinese and Western philosophical traditions. Rejecting Kant’s “epistemological path” as deficient, Mou argues that knowledge of the transcendent is possible through moral practice, as demonstrated by the Confucian tradition. His merging of immanence and transcendence implies a different relation between ethics and religion compared with the way Kant himself conceived that relation. Despite the emphasis on practice in his understanding of Confucian spirituality, Mou’s approach is significantly different from a Dewey inspired Pragmatist approach to claims about transcendence. The paper contextualizes the theoretical choices in the development of Mou’s philosophy within China’s historical encounter with Dewey’s Pragmatism, and Mou’s own perception of his mission in a period of cultural crisis.